2005
DOI: 10.1203/01.pdr.0000155946.82230.2e
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis during Reoxygenation Has an Early Detrimental Effect on Neuronal Metabolic Activity

Abstract: We recently showed that acidosis is protective during hypoxia and detrimental during reoxygenation. We hypothesized that the detrimental effect of acidosis during reoxygenation was due to a negative effect on mitochondrial function. Human postmitotic NT2-N neurons were exposed to 3 h of hypoxia and glucose deprivation and then reoxygenated for 0, 1, 4, 9, or 21 h. The detrimental effect of acidotic reoxygenation on metabolic activity was evident already after 1 h of reoxygenation, when MTT [3-(4, 5-dimethylthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Ischemic injury can cause the activities of mitochondrial complexes to decrease. ,, Previous studies have shown that acidosis can increase the protein levels of several complexes during hypoxia or increase the activity of complex IV during OGD. These studies and our results, which show that mild acidosis attenuates OGD-induced reductions in the activities of mitochondrial complexes I and II, demonstrate that acidosis protected mitochondrial function during OGD by targeting electron transport chain complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Ischemic injury can cause the activities of mitochondrial complexes to decrease. ,, Previous studies have shown that acidosis can increase the protein levels of several complexes during hypoxia or increase the activity of complex IV during OGD. These studies and our results, which show that mild acidosis attenuates OGD-induced reductions in the activities of mitochondrial complexes I and II, demonstrate that acidosis protected mitochondrial function during OGD by targeting electron transport chain complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme assays were performed at 30°C in 200 µl final volume using a SPECTRAmax PLUS 384 Micro plate Spectrophotometer (Molecular Devices). Succinate-cytochrome c reductase (complex II+III) activity was measured as ferricytochrome c reduction, whereas cytochrome c oxidase (complex IV) activity was determined as the initial rate of ferrocytochrome c oxidation (Froyland et al 2005). All samples were measured three times, and enzyme activities were expressed as nanomole per minute per milligram fibroblast protein.…”
Section: Controlsmentioning
confidence: 99%